Beyond Pharmacology: Transitioning Off Incretin-Based Therapies and the Role of Lifestyle Interventions in Weight Maintenance - Buzek, Emilia; Tomaszewska, Anna; Kaczmarek, Marcelina; Pojawa, Maria; Chudzik, Aleksandra; Prządka, Jagoda; Witkowska, Wioletta (Quality in Sport, 2026)
Incretin-based therapies facilitate substantial weight loss; however, nearly 68% of patients discontinue treatment within the first year. When patients withdraw, they often regain weight quickly because their metabolism slows down from losing muscle, and their appetite increases, a problem called "food noise." No standard clinical guidelines exist for this transition. This review aims to identify practical lifestyle interventions that support weight maintenance and health after cessation of these medications. A targeted literature search of PubMed/MEDLINE, Scopus, and Google Scholar was conducted. Through May 2026, we identified English-language, peer-reviewed studies on post-withdrawal metabolic changes, body composition, nutrition, and behavioral strategies. The problem of preventing weight regain calls for structured clinical transition strategies. A balanced, eucaloric diet is preferred. Studies suggest that dietary interventions can help patients, as sufficient protein intake supports energy expenditure. Progressive resistance training is critical for restoring muscle mass, which frequently declines during active weight reduction. The active treatment phase should be used to establish long-lasting habits. Discontinuation of pharmacotherapy poses a significant challenge, as maintaining weight loss afterward can be extremely difficult for patients. If cessation is inevitable, the medical approach should integrate tailored nutrition, structured physical activity, and ongoing behavioral support.